2000
DOI: 10.1097/00007890-200004270-00007
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of H-2kb-Transgenic Adrenocortical Cells in the Mouse Having Undergone an Adrenalectomy

Abstract: In conclusion, a model of cellular adrenocortical transplantation was established. The results show that syngeneic transplantation resulted in physiological corticosterone levels early after transplantation, whereas fully MHC-incompatible grafts were rejected. Recipients of Kb-transgenic grafts showed unimpaired adrenocortical function, but did not tolerize toward Kb-transgenic skin grafts. Possible mechanisms include a local immunomodulatory effect of glucocorticoids secreted by the graft and a low immunogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…Our research group previously demonstrated that selected allografts (adrenal cortex cells and pancreatic islet cells) with an isolated MHC class I disparity survive indefinitely (4,10). These results were confirmed by Kneteman et al who reported that MHC class I up-regulation is not associated with an acceleration of pancreatic islet cell rejection (11).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Our research group previously demonstrated that selected allografts (adrenal cortex cells and pancreatic islet cells) with an isolated MHC class I disparity survive indefinitely (4,10). These results were confirmed by Kneteman et al who reported that MHC class I up-regulation is not associated with an acceleration of pancreatic islet cell rejection (11).…”
Section: Discussionsupporting
confidence: 72%
“…ANDREA SCHNEIDER, 1 MASOUMEH ATTARAN, 1 KLAUS F. GRATZ, 2 JOERG S. BLECK, 1 MICHAEL WINKLER, 3 MICHAEL P. MANNS, 1 AND MICHAEL OTT 1,4 Background. Partial correction of metabolic liver disease by hepatocyte transplantation requires infusion of a large number of cells into the portal vein.…”
Section: Intraportal Infusion Of 99m Technetium-macro-aggregrated Albmentioning
confidence: 99%
See 3 more Smart Citations